Extracting the QCD Cutoff Parameter Using the Bernstein Polynomials and the Truncated Moments - A. Mirjalili; M. M. Yazdanpanah; Z. Moradi (Advances in High Energy Physics)
Since there are not experimental data over the whole range of x-Bjorken variable, that is, 0<x<1, we are inevitable in practice to do the integration for Mellin moments over the available range of experimental data. Among the methods of analysing DIS data, there are the methods based on application of Mellin moments. We use the truncated Mellin moments rather than the usual moments to analyse the EMC collaboration data for muon-nucleon and WA25 data for neutrino-deuterium DIS scattering. How to connect the truncated Mellin moments to usual ones is discussed. Following that we combine the truncated Mellin moments with the Bernstein polynomials. As a result, Bernstein averages which are related to different orders of the truncated Mellin moment are obtained. These averaged quantities can be considered as the constructed experimental data. By accessing the sufficient experimental data we can do the fitting more precisely. We do the fitting at leading order and next-to-leading order approximations to extract the QCD cutoff parameter. The results are in good agreement with what is being expected.